THE RELATIONSHIP BETWEEN DECISION-MAKING AND GAME INTELLIGENCE WITH BASKETBALL STATISTICS - Németh, Kata; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2021)
Introduction: basketball is one of the most popular teams sports worldwide. It is generally regarded as the second most popular sport globally, with around 450 million registered players (RÁTGÉBER et al., 2019). The attention, decision-making, interaction with the participants, and recovery of a basketball player are complex. It can be influenced by internal and external factors as well as by different stimuli. The current mental and physical state of athletes affects their performance. Experience, reception and adaptation of developmental stimuli determine performance during the game. Cognitive abilities, executive functions, and inhibition are all psychological processes that can help or hinder concentration. It is essential to assess and measure to enhance sports performance and provide objective support for our subjective assumptions. Many technical and tactical elements characterize basketball, but it is also essential to have relevant motor and affective skills when making decisions. Players need to adapt to sudden and varied stimuli and make the most intelligent and appropriate decision to achieve a positive outcome. Live statistics may indicate the effectiveness of decision-making during the game. In the present study, we analyzed the results of the Color-Word Interference Test and Trail Making Test prior to and after the games.